2017
DOI: 10.1002/ijgo.12251
|View full text |Cite
|
Sign up to set email alerts
|

Shock progression and survival after use of a condom uterine balloon tamponade package in women with uncontrolled postpartum hemorrhage

Abstract: The ESM-UBT device arrests hemorrhage, prevents shock progression, and is associated with high survival rates among women with uncontrolled PPH from uterine atony.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 16 publications
1
28
0
Order By: Relevance
“…For example, in a series of women with uncontrolled hemorrhage refractory to all other interventions, 160 (98%) of 163 survived after placement of a pre‐packaged condom uterine balloon . Additionally, among 306 consecutive women with uncontrolled PPH across 117 facilities, the survival rate was 99.4% if the UBT device was placed before advanced shock (objective signs of neurological and/or cardiovascular compromise) . Other evidence includes independently performed near‐miss surveys, impact and cost‐effectiveness studies, and the experiences of senior obstetricians’ and midwives’ in averting deaths and hysterectomies from their 14 countries and beyond (Table ).…”
Section: Quotes From 2017 Obgyn Meetingsmentioning
confidence: 99%
“…For example, in a series of women with uncontrolled hemorrhage refractory to all other interventions, 160 (98%) of 163 survived after placement of a pre‐packaged condom uterine balloon . Additionally, among 306 consecutive women with uncontrolled PPH across 117 facilities, the survival rate was 99.4% if the UBT device was placed before advanced shock (objective signs of neurological and/or cardiovascular compromise) . Other evidence includes independently performed near‐miss surveys, impact and cost‐effectiveness studies, and the experiences of senior obstetricians’ and midwives’ in averting deaths and hysterectomies from their 14 countries and beyond (Table ).…”
Section: Quotes From 2017 Obgyn Meetingsmentioning
confidence: 99%
“…Previous research by the authors has clearly demonstrated that uterine balloon tamponade can both avert hysterectomies and other surgical interventions as well as arrest hemorrhage and shock progression Burke et al, 2017). It appears there may have been numerous missed opportunities to avert emergency surgical intervention among those surveyed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The authors' work has shown that if applied in a timely fashion, uterine balloon tamponade arrests hemorrhage, halts shock progression , averts nearly all deaths and emergency hysterectomies Burke et al, 2017), is "safe" and "highly cost-effective" (Mvundura et al, 2017), and can be placed successfully by any cadre, including illiterate front-line health workers . Deploying a UBT device involves placing a balloon within the uterine cavity and inflating it until hemorrhage ceases.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, commercial UBT devices have become available for use in atonic postpartum hemorrhage; however they are often unaffordable in resource limited settings. Over the past eight years the authors have designed, implemented, refined, and studied [5, 6] an evidence-based package called Every Second Matters for Mothers-UBT (ESM-UBT). The ESM-UBT is a simple innovation that consists of a condom fastened to a 24 French Foley catheter by string.…”
Section: Introductionmentioning
confidence: 99%
“…The condom balloon is inflated until the bleeding is arrested. The ESM-UBT device is safe and extremely effective in saving women's lives, especially when placed before the advanced stages of shock [6]. The authors have supported implementation of the ESM-UBT package across several low-resource countries including South Sudan, Kenya, Sierra Leone, Senegal, Zambia, Ghana, Nepal, India, Uganda, Honduras, Peru, Tanzania, and Cote' Ivoire.…”
Section: Introductionmentioning
confidence: 99%